The Effect of Some Chemical Materials against Virulence Factors of Candida Ssp Isolated from UTI Patients - Fatima Abdul Hussein Mejbel (Journal of Global Pharma Technology, 2018)
During the period from September 2016 to December 2017, a total of 135 urine samples were collected from urinary tract infection patients attending to AL-Zahraa Hospital in AL-Najaf Governorate. The present study was conducted to isolate and identify Candida spp. isolated from urinary tract infection patients by different methods including direct examination , laboratory culture , biochemical test and by modern techniques (Api Candida kit) and determine the virulence factors phenotypic to Candida spp which involved (bio film formation, phospholipase and germ tube).The percentage of females to males was as following , female (84) 62.2 % (21) infected and male (51) 37.8% (1) infected with all age categories. The results in this study are explain that is some Candida spp. such as C. albicans, have high susceptible to eugenole follow by phenol and umbellulone. The efficiency of some chemical substances such as (eugenole, umbellulone, and phenol) was evaluated to inhibit the growth of Candida ssp as well as some virulence factors such as bio film formation, germ tube and phospholipase which were studied in this research. Statistically analysis results have been significance difference between the results of the substance concentrations and the concentrations of the different other substances.